(untitled) (Journal of Mechanical Engineering, 2009)
The effect of small uniform magnetic field on separation of a binary mixture for the case of a fully developed natural convection between two heated inclined plates has been investigated in this paper. Neglecting the induced electric field the equations governing the motion, temperature and concentration are solved by simple perturbation technique, in terms of dimensionless parameter measuring buoyancy force. The expressions for velocity, temperature and concentration are obtained. The effects of Hartmann number (M), thermal diffusion number (td), the buoyancy force parameter (N) and the inclination angle (Ï) of the plates with the horizontal are studied on the flow and heat transfer quantities. Keywords: Natural convection, thermal diffusion, magnetic field, incompressible fluid, binary mixture. doi:10.3329/jme.v39i2.1848 Journal of Mechanical Engineering, Vol. ME39, No. 2, Dec. 2008 65-70